Firm-Specific Capital, Nominal Rigidities, and the Taylor Principle - Tommy Sveen; Lutz Weinke (Norges Bank, 2006)
In the presence of firm-specific capital the Taylor principle can generate multiple equilibria. Sveen and Weinke (2005b) obtain that result in the context of a Calvo-style sticky price model. One potential criticism is that the price stickiness which is needed for our theoretical result to be relevant from a practical point of view is somewhat to the high part of available empirical estimates. In the present paper we show that if nominal wages are not fully flexible (which is an uncontroversial empirical fact) then the Taylor principle fails already for some minor degree of price stickiness. We use our model to explain the consequences of both nominal rigidities for the desirability of alternative interest rate rules.
hdl:11250/2498370
Keywords: E22; E31; 330; nominal rigidities; aggregate investment; monetary policy